Supreme courtship a novel - Buckley, Christopher 1952- (Twelve, 2008)
When a television judge ends up on the Supreme Court, romance and the fate of a presidential election take center stage in this comic political satire.
Keywords: United States -- Supreme Court -- Fiction; Judges -- Fiction; Television personalities -- Fiction; USA; Washington (D.C.) -- Fiction; Political fiction; Legal stories